Private Sector Participation in Market-Based Energy-Efficiency Financing Schemes : Lessons Learned from Romania and International Experiences - World Bank (Washington, DC, 2014)
Financing of energy-efficiency (EE) projects in a country almost always commences with public funds. Examples are energy service company (ESCO) businesses in the United States and Canada that were able to take advantage of public funds for public buildings (World Bank 1999), most of the EE funds worldwide as compiled in a recent Alliance to Save Energy report (ASE 2002), or various EE projects funded by international financial institutions (IFIs). A sustainable EE business can, however, develop only if public funding is complemented by funding from the private sector. In the past few years, some equity funds with IFI and private sector participation have sprung up, such as the Renewable Energy and Energy Efficiency Fund for Emerging Markets (REEF) and Dexia-FondElec, and several IFI/GEF projects in transition and developing countries have experimented with various features that would reduce the barriers for private sector involvement in financing EE projects. The longest running of those financial schemes is the Hungary IFC/GEF Guarantee Fund. In light of the lessons learned from those projects, this report concentrates on the example of Romania, where implementation of a World Bank GEF project with a market-based EE financing mechanism has just started. Until recently, Romanian energy consumers were enjoying energy prices well below world market prices. With restructuring of the energy sector, the energy price level is now going up and subsidies are being phased out. Together with restructuring and privatization in the industrial sector, there are now incentives for investments in energy efficiency that would reduce costs and improve the competitiveness of Romanian companies.